ASFV pA151R negatively regulates type I IFN production via degrading E3 ligase TRAF6 - You Li; You Li; You Li; You Li; Li Huang; Hui Li; Hui Li; Hui Li; Hui Li; Yingqi Zhu; Yingqi Zhu; Yingqi Zhu; et al. (Frontiers in Immunology, 2024)
African swine fever (ASF) caused by African swine fever virus (ASFV) is a highly mortal and hemorrhagic infectious disease in pigs. Previous studies have indicated that ASFV modulates interferon (IFN) production. In this study, we demonstrated that ASFV pA151R negatively regulated type I IFN production. Ectopic expression of pA151R dramatically inhibited K63-linked polyubiquitination and Ser172 phosphorylation of TANK-binding kinase 1 (TBK1). Mechanically, we demonstrated that E3 ligase TNF receptor–associated factor 6 (TRAF6) participated in the ubiquitination of TBK1 in cGAS-STING signaling pathway. We showed that pA151R interacted with TRAF6 and degraded it through apoptosis pathway, leading to the disruption of TBK1 and TRAF6 interaction. Moreover, we clarified that the amino acids H102, C109, C132, and C135 in pA151R were crucial for pA151R to inhibit type I interferon production. In addition, we verified that overexpression of pA151R facilitated DNA virus Herpes simplex virus 1 (HSV-1) replication by inhibiting IFN-β production. Importantly, knockdown of pA151R inhibited ASFV replication and enhanced IFN-β production in porcine alveolar macrophages (PAMs). Our findings will help understand how ASFV escapes host antiviral immune responses and develop effective ASFV vaccines.